Pengaruh Promosi, Kualitas Produk dan Inovasi Produk Terhadap Pembelian Ulang Texcer.hot Bangsri - Ardani, Adelia Kusuma; Ali, Ali (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This research aims to analyze the influence of promotion, product quality, and product innovation on repurchase decisions at Texcer.hot in Bangsri, considering the importance of customer loyalty in the competitive retail industry. The method used is quantitative with a survey design, involving 104 respondents selected through purposive sampling. Data was collected using a questionnaire covering demographics, promotion, product quality, product innovation, and repurchase decisions.The data was analyzed using SPSS software. The validity test results showed that most of the question items were valid, while the reliability test indicated that all variables had a Cronbach's Alpha value above 0.60, signifying good reliability. The normality test revealed that the data was not normally distributed; therefore, an appropriate analysis method was employed. The regression analysis results demonstrate that the variables of promotion, product quality, and product innovation have a significant effect on repurchase decisions, with regression coefficients of 0.231, 0.596, and 0.107, respectively. The F-test shows that, simultaneously, the three independent variables have a significant influence on the dependent variable.Thus, this study concludes that to increase repurchase decisions, the company needs to focus on effective promotional strategies, improving product quality, and relevant product innovation. These findings are expected to provide insights for marketing practitioners in designing better strategies to attract and retain customers.